The influence of professional competence and leadership of school principals on the performance of physical education teachers in state Junior High School, Parongpong District, West Bandung Regency - Siman, Asep; Supriadi, Dedi; Kadarisman, Vicki Ahmad (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study aims to examine the influence of teachers' professional competence and principals' leadership on the performance of physical education teachers at State Junior High School, Parongpong District, West Bandung Regency. The research method uses an explanatory survey approach with a population of 12 physical education teachers. Data was collected through a questionnaire that had been tested for validity and reliability, then analyzed using validity tests, reliability tests, classical assumption tests, t tests, F tests, and simple linear regressions with the help of SPSS software version 26. The results of the study show that teachers' professional competence has a positive and significant influence on teacher performance. In addition, the leadership of the principal also has a positive and significant effect on teacher performance, where the principal who effectively provides guidance, motivation, and creates a conducive work climate can increase the professionalism and work spirit of teachers. Simultaneously, the professional competence and leadership of the principal together made a significant contribution to improving the performance of physical education teachers. These findings affirm the importance of the continuous development of teacher competencies and the active role of the principal's leadership in creating a learning environment that supports the improvement of the quality of physical education.